(untitled) (Bangladesh Journal of Botany, 2023)
Water stress during flowering stage is a key factor effecting maize productivity in India. Mahalanobis D2 method was used to group one hundred and thirty-three inbred lines based on their phenotypic performance under waters stress condition. Fifteen selected lines were crossed in half diallel fashion to produce 105 direct F1 crosses which were then evaluated under water stress and non-stress condition. Negative correlation was observed between parents mahalanobis distance and grain yield suggesting parents with diverse phenotypic expression need not always produce heterotic hybrids. Mid-parent heterosis showed linear relationship with grain yield and none of the combining ability effects showed significant association with grain yield. Thus, per se performance of inbred lines across the traits under water stress situation has to be considered in selection of parents for production of heterotic hybrids. Bangladesh J. Bot. 52(4): 915-923, 2023 (December)